Evaluation of the irritancy and hypersensitivity potential following topical application of didecyldimethylammonium chloride. (3rd July 2016) - Anderson, Stacey E.; Shane, Hillary; Long, Carrie; Lukomska, Ewa; Meade, B. Jean; Marshall, Nikki B.
Abstract: Didecyldimethylammonium chloride (DDAC) is a dialkyl-quaternary ammonium compound that is used in numerous products for its bactericidal, virucidal and fungicidal properties. There have been clinical reports of immediate and delayed hypersensitivity reactions in exposed individuals; however, the sensitization potential of DDAC has not been thoroughly investigated. The purpose of these studies was to evaluate the irritancy and sensitization potential of DDAC following dermal exposure in a murine model. DDAC induced significant irritancy (0.5 and 1%), evaluated by ear swelling in female Balb/c mice. Initial evaluation of the sensitization potential was conducted using the local lymph node assay (LLNA) at concentrations ranging from 0.0625–1%. A concentration-dependent increase in lymphocyte proliferation was observed with a calculated EC3 value of 0.17%. Dermal exposure to DDAC did not induce increased production of IgE as evaluated by phenotypic analysis of draining lymph node B-cells (IgE  +  B220 + ) and measurement of total serum IgE levels. Additional phenotypic analyses revealed significant and dose-responsive increases in the absolute number of B-cells, CD4  +  T-cells, CD8  +  T-cells and dendritic cells in the draining lymph nodes, along with significant increases in the percentage of B-cells (0.25% and 1% DDAC) at Day 10 following 4 days of dermal exposure. There was also a significant and dose-responsive increase in the number of activated CD44  +  CD4  +  and CD8  +  T-cells and CD86  +  B-cells and dendritic cells following exposure to all concentrations of DDAC. These results demonstrate the potential for development of irritation and hypersensitivity responses to DDAC following dermal exposure and raise concerns about the use of this chemical and other quaternary ammonium compounds that may elicit similar effects.